INTEGRASI STEAM PROJECT BASED LEARNING UNTUK MENGEMBANGKAN KECAKAPAN KARAKTER MAHASISWA PADA PEMBELAJARAN MATEMATIKA - Andri Kristianto Sitanggang (Universitas Negeri Medan, 2026)
This study examines the integration of the STEAM-Project Based Learning (STEAM-PjBL) model to develop students' character qualities in mathematics education. The primary issue addressed is the tendency for mathematics learning to be overly theoretical and rigid, thereby failing to facilitate effective affective development. Through a literature analysis, it was found that the synergy between science, technology, engineering, arts, and mathematics in real-world projects effectively enhances students' creativity, independence, and collaborative character. The